Change in Negative Affective Bias following a Single Ketamine Treatment for Treatment-Resistant Depression - Harvey, Anna J.; Nikolin, Stevan; Chand, Nicholas; Flanney, William; Tan, Liyi; Moffa, Adriano; Loo, Colleen K.; Martin, Donel M. (Depression and Anxiety, 2023)
Ketamine has recently emerged as a highly effective new treatment for people with treatment-resistant depression with rapid antidepressant effects. However, these effects are often short lasting, and the potential cognitive mechanisms underlying the therapeutic effects, such as effects on emotional processing bias, remain poorly understood. In the present study, we explored potential changes in emotional and cognitive processing following a single treatment of subcutaneous ketamine in a randomised double-blind controlled study with an active control. Participants with treatment-resistant major depressive disorder (MDD) were recruited from a single site from the Ketamine for Adult Depression Study (KADS Trial) and were randomly assigned to receive racemic ketamine hydrochloride (n=10) or midazolam hydrochloride (n=11) in a 1 : 1 ratio. A healthy control sample (n=23) was recruited to attend a single experimental session without any treatment. All MDD participants completed mood ratings and cognitive assessments prior to and one day after a single randomised treatment. The results showed no significant differences in performance changes after treatment across the majority of emotion-related (i.e., Emotional Stroop Task, Affective Go/No-Go Task) and cognitive (Ruff 2 and 7 Selective Attention Test, Controlled Word Association Test) outcome measures. Participants who received ketamine showed a significant improvement in a negative processing bias test (i.e., The Scrambled Sentence Task; Cohen’s d=.67, p=.016), which was not significantly associated with improvement in psychological symptoms (r=−.662, p=.074). The results from this exploratory study suggest that a single ketamine treatment may modulate negative affective bias. Limitations to this study included the small sample size and lack of follow-up. Future larger trials are required to confirm this finding.